Definitions and methods of measuring and reporting on injurious falls in randomised controlled fall prevention trials: a systematic review - Schwenk, Michael; Lauenroth, Andreas; Stock, Christian; Rodríguez Moreno, Raquel; Oster, Peter; Hauer, Klaus (BMC medical research methodology, 2012)
The standardisation of the assessment methodology and case definition represents a major precondition for the comparison of study results and the conduction of meta-analyses. International guidelines provide recommendations for the standardisation of falls methodology; however, injurious falls have not been targeted. The aim of the present article was to review systematically the range of case definitions and methods used to measure and report on injurious falls in randomised controlled trials (RCTs) on fall prevention.
Published: 17 April 2012
Gesehen am 12.06.2018